RIS-assisted multi-user beam tracking system and hardware experiment - DING Chenlong; XU Wenjun; ZHANG Hongtao (Dianxin kexue)
Reconfigurable intelligent surface (RIS) effectively improves the performance of 6G communication systems by intelligently controlling the electromagnetic propagation path. However, the integration of a large number of reflecting elements in RIS increases the complexity of multi-beam control and enlarges the codebook search space, leading to insufficient real-time control capabilities and difficulties in multi-user beam tracking. To enhance the applicability of RIS in multi-user mobile scenarios, an innovative inverse diffraction-based field source iterative model was proposed to rapidly generate near- and far-field multi-user control codebooks. A RIS-assisted single base station positioning scheme was designed to sense the movement of users and switch beams in real-time. A prototype of a RIS-assisted multi-user beam tracking system was developed, enabling fast beam alignment during multi-user mobility. Experimental results show that millisecond-level beam switching can achieve real-time information transmission for mobile multi-users.